PROCEDURAL E-SCAFFOLDING IN IMPROVING STUDENTS’ PHYSICS PROBLEM SOLVING SKILLS - Saman, Muhammad Iqbal; Koes-H, Supriyono; Sunaryono, Sunaryono (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
The purpose of this study was to design scaffolding that is connected to an ICT system (e-scaffolding) which was implemented with blended learning to improve students’ physics problem solving skills (PSS). The research method used is Borg & Gall research method and the effectiveness test used is T-test in analyzing whether there are differences physics PSS in the experimental and control classes. This article describes scaffolding systems that focus in procedural types which using prompt questions and facts found during the implementation of this product. The results showed that the developed e-scaffolding was appropriate to be used for several examinations after being evaluated by experts and practitioners. In a limited implementation, e-scaffolding has proven not to be out of the social constructivist scope and adapted to the actual abilities of students. At effectiveness test, e-scaffolding is able to connect between students in solving problems both in synchronous and asynchronous collaboration. In addition, e-scaffolding is able to split problem categories that students are experts and beginners, giving shape to performance and increasing students’ physics PSS. So, it can be concluded that e-scaffolding has been successfully developed. Suggestions for further research have been presented in this article.